Dot plot supports 7th grade students in learning informal inferential reasoning (IIR) - L Fakhmi; H Windria (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
In recent years, there have been many changes in the educational world that have been done a research in stages. The changes can be found out in term of material content, methods, models, and strategies. The changes reffered to in this study are in the sense of statistics known as Informal Inferential Reasoning (IIR). Simply put, IIR can be interpreted as a withdrawal of inferences from samples that apply to the population. Therefore, the researcher suggests the need for a visual representation in studying IIR in order to draw conclusions from a given data. The visual representations referred to in this research report focus on the dot plot. In addition to the dot plot, a series of learning activities in learning IIR has been designed using Realistic Mathematics Education (RME) as an approach in learning. The method used in this research is design research. This research was conducted in SMPN 7 Tangerang Selatan with research subjects as many as six students taken from one of the 7th grade in the school. As for the results obtained in this study, dot plot is able to help students to draw conclusions from samples to populations based on data presented on the graph.